The Acute Effects of Electronic Cigarette Vaping and Tobacco Cigarette Smoking on Choroidal Thickness in Young, Healthy, Habitual, Dual Smokers - Olga E. Makri; Athina Pallikari; Konstantinos Kagkelaris; Stylianos N. Mastronikolis; Georgios Karanasios; Chrysanthos Symeonidis; Panagiotis Plotas; Constantine D. Georgakopoulos (Toxics, 2020)
The present study aims to evaluate and compare the acute effects of tobacco cigarettes (TC) smoking and electronic cigarette (EC) vaping on foveal and choroidal thickness (CT) in young, healthy, dual smokers. Participants underwent four trials: 5 min TC; 5 min EC; 30 min EC; and 60 min nothing (sham trial). Scans before and immediately after each trial were obtained using spectral domain optical coherence tomography with the enhanced depth imaging mode. Changes in central foveal thickness (CFT), subfoveal choroidal thickness (SFCT), and CT at fourother points, 500 μm and 1000 μm temporally and nasally to the fovea, were measured. Forty-seven participants (33 male, 14 female; mean age 24.85 ± 1.57 years) were included. They smoked 13.53 ± 5.27 TCs/day for 6 ± 2.3 years and vaped ECs for the past 2.4 ± 1.08 years. We did not observe any statistically significant change in SFCT, CFT, and CT of the other points after any of the fourtrials. The acute changes in CFT and CT after EC vaping or TC smoking did not differ significantly compared to the sham trial. Smoking and vaping does not seem to result in statistically significant acute alterations in foveal and CT in young, dual smokers.